UJI AKTIVITAS TABIR SURYA EKSTRAK HERBA MENIRAN (Phyllanthus niruri L.) - Nabila, Sahira Fara; Koesnarpadi, Soerja; Widodo, Nanang Tri; Isyahro, Novia Rahmawati; Marliana, Eva (Jurusan Kimia FMIPA UNMUL, 2022)
Tests of sunscreen activity of meniran (Phyllanthus niruri L.) herbs extract has been done. The methodwas carried out using an UV-Vis spectrophotometer in vitro based on the method of A. J. Petro. The sunscreenactivity based on the value of the Sun Protection Factor (SPF) meniran herbs extract, respectively, was 1,826;3,337; 6,096; 11,132 and 20,354. The SPF value of sunscreen activity showed that meniran herbs extract has aminimum to ultra protection category.